Effects of graphene/PLGA composite scaffolds on proliferation and differentiation of bone marrow mesenchymal stem cells - Zheng, Ao; Cao, Lingyan; Liu, yang; Wu, Jiannan; Jiang, Xinquan (Ecomaterials, 2023)
Objective: This study aimed at fabricating three-dimensional porous graphene (G)/poly(lactic-co-glycolic acid (PLGA) composite scaffolds and establishing the potential for further application of G/PLGA porous scaffolds in bone tissue engineering. Methods: Different concentrations of graphene was mixed with PLGA (G/PLGA, wt. ‰: 0, 0.5‰, 5‰). Results: Scanning electron microscopy confirmed the inner connected porous structure of the three-dimensional G/PLGA scaffold as well as the uniform distribution of graphene in the scaf-folds. CCK-8 test indicated that G/PLGA porous scaffolds had no obvious cytotoxicity. Compared with BMSCs seeded on PLGA scaffold, the ALP activity of BMSCs seeded on the G/PLGA scaffolds increased and the expression of bone related genes was significantly up-regulated with increase of G concentration. G/PLGA porous scaffold containing 5‰ graphene showed more obvious effects on osteogenic differentiation. Conclusions: The G/PLGA three-dimensional porous scaffold prepared in this research possessed good biocom-patibility and could promote osteogenic differentiation of BMSCs in vitro. Thus, it has been expected to be used as a scaffold for bone tissue engineering.